Model-based Design for RS Encoder and Decoder - Nie, Yang (International Journal of Computer Science and Information Technology, 2024)
In this paper, an efficient design methodology of the Reed-Solomon (RS) encoder/decoder is proposed via Model-Based Design (MBD), which is focused on the development process from requirements development, design, implementation and testing. The design code can be automatically generated, and the testing-bench for RS encoders/decoders can also be automatically created. Compared to traditional design methods, the MBD approach can improve product quality and reduce development time.